Enzymatically synthesized lactone-based copolymer and gelatin nanofibrous blends loaded with an olive leaf phenolic compound - Turan, Cansu Ülker; Derviscemaloglu, Mete; Guvenilir, Yuksel (Elsevier, 2024)
In literature, studies that cover a biomedical application of an enzymatically synthesized, thus more biocompatible, polymer are limited. Therefore, originality of this research aimed to be improved by examination of an enzymatically synthesized lactone-based copolymer, which was obtained based on previous experiences, as a component of a nanofibrous wound dressing. Moreover, obtaining a synergetic effect was purposed by blending this synthetic copolymer with a natural polymer. In this context, the prospect of an oleuropein-loaded poly (omega-pentadecalactone-co-delta-valerolactone)/gelatin (PDL-VL/Gel) electrospun nanofibrous membrane as wound dressing for treatment of skin infections was investigated. It was preferred to provide the antibacterial activity by the addition of a phenolic compound found in olive leaf extract, oleuropein. Varied amounts of oleuropein (10-75%, w-v) were electrospun together with PDL-VL/Gel (equal volume ratio) polymer blend (fiber diameters ranged between 560-806 nm) and several characterizations (morphological and molecular structure, wettability characteristics, and thermal behavior) were applied to examine the oleuropein incorporation. According to antibacterial activity test results, 75% oleuropein loading ratio was found to be appropriate for the treatment of skin wounds infected by Gram-negative (E. coli) and Gram-positive (S. aureus and B. subtilis) bacteria. Additionally, nanofibrous membranes did not lead to cytotoxicity, and oleuropein content further enhanced the viability of fibroblasts. To conclude, the presented antibacterial nanofibrous membrane is a promising biomaterial for the treatment of wound infections and acceleration of healing process.
Keywords: Enzymatic polymerization; Electrospinning; Wound healing; Oleuropein; Gelatin